Facilitators and barriers to Tuberculosis case notification among private health facilities in Kampala Capital City, Uganda. - Veronica Kembabazi; Julius Ssentongo; Elizeus Rutebemberwa (PLoS ONE)
Introduction Private Health Facilities (PHFs), Uganda's main healthcare providers, are indispensable stakeholders in the national tuberculosis (TB) program's efforts to improve TB case notification and combat the epidemic. However, notification rates remain relatively low in PHFs compared to public providers. In this study, we sought to assess facilitators and barriers to TB case notification among private facilities in Kampala Capital City. Methods We conducted a cross-sectional study utilizing a mixed-methods approach to assess facilitators and barriers to TB notification in Kampala Capital City between March and July 2022. For the quantitative strand of the study, we interviewed the TB focal persons at 224 PHFs using a structured questionnaire and for the qualitative, we conducted 14 key informant and in-depth interviews with Ministry of Health-Uganda staff, and TB focal persons at the Kampala Division administration level and at the PHFs. The quantitative analysis involved Modified Poisson regression and the qualitative analysis was carried out using thematic analysis to identify the facilitators and barriers to TB case notification. Results Of the 224 PHFs surveyed, the majority, 39.3%(88), were facilities in Nakawa division and 55.4% (124) of the respondents were male, with a mean age of 32.6 years (SD = 8.6). We found that the prevalence of TB case notification was significantly lower for facilities in Kawempe (PR 0.16; 95%CI 0.05,0.47) and Nakawa (PR 0.39, 95%CI 0.21,0.73). Notification was lower among facilities that had no guide for TB screening and diagnosis (PR 0.50; 95%CI 0.25,0.97) and among those facilities where training of other health workers at the facility in TB diagnosis was unknown (PR 0.35; 95%CI 0.13,0.93). Qualitative data showed that the main facilitators of TB case notification were: regular engagements between the NTLP and private health providers and, provision of materials and support to conduct case finding, while the main barriers included TB stigma, lack of resources such as TB diagnostic facilities. Conclusions PHFs in Kampala Capital City are receptive to programmatic TB case notification. However, they need regular supervision and engagement activities to ensure that they have updated knowledge, equipment and funding support to carry out TB case notification according to policy.